Education, gender, religion, politics: What priorities for cultural integration policies in Switzerland? - Pierre Kohler (Graduate Institute of International and Development Studies, 2012)
This paper explores cultural integration paths of eight migrant groups in Switzerland. It specifically analyzes the evolution of objective behaviors and subjective attitudes of migrants from the first to the second generation. In order to deepen the analysis, the cultural integration of migrants is further examined from different perspectives: across cohorts (older vs. younger migrants) and across types of couples (individuals in endogamous vs. mixed couples). Gender differences are also paid attention to. First, behaviors are examined by looking at performances of migrants at school (educational attainment and gender gap). As women play a key role in the transmission of cultural traits and the socialization of the second generation, the focus then turns to their position in the couple (marriage, intermarriage, age and education gap between partners, early marriage, cohabitation, fertility, divorce) and in the labor market (labor force participation). Finally, this paper proposes to look at migrants' use of language, their feelings towards Switzerland, as well as their attitudes towards gender, religious and political issues. Evidence points to overall convergence. As the most striking and lasting differences across groups do not pertain to educational achievement, religious or political attitudes but to gender-related attitudes and, even more, to gender-related behaviors in endogamous couples, it appears that migration-related gender issues and migration-specific household dynamics should be taken into account in the design of future cultural integration policies.
Keywords: F22; Z10; Z13; 330; immigration; migration; culture; integration; Switzerland; Einwanderung; Soziale Integration; Kulturelle Identität; Migranten; Schweiz